ANT 2013/14 : AWI airborne Snow Radar data over western Dronning Maund Land at the EPICA DML ice core site, Slessor Ice Stream, Stancomb-Wills Ice Stream, and Antarctic Peninsula (CoFi Structure project) - Daniel Steinhage; Veit Helm (PANGAEA, 2025)
This dataset contains airborne radar data acquired using the AWI Snow Radar (SNOW) system during the Antarctic season of 2013/14. The profiles cover the EPICA DML ice core site, Slessor Ice Stream, Stancomb-Wills Ice Stream, and Antarctic Peninsula. The data are available as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams.